Synthesis and characterization of the photoswitchable poly(methyl methacrylate- random-methacrylate spirooxazine) - Nguyen,Tam Huu (2019)
Abstract The photoswitchable poly(methyl methacrylate-random-methacrylate spirooxazine) was synthesized via atom transfer radical polymerization with the feed mole ratio of MMA/MSp comonomer of about 5.5/1. Well-defined poly(methyl methacrylate- random-methacrylate spirooxazine) have been obtained with the average molecular weight (Mn) of 6500 g/mol and polydispersity of 1.21. The structure and properties of the resulting copolymers were characterized by proton nuclear magnetic resonance (1H NMR), gel permeation chromatography, Fourier Transform infrared, UV-visible spectroscopy, and differential scanning calorimetry. Moreover, the copolymer exhibited the erasable and rewritable photoimaging on the solid state film which could to be as potential candidate for optical data storage materials.